Garum or Grain? Crimea and the Provisioning of Constantinople (7th to 9th centuries) - Curta, Florin (Studia Ceranea, 2023)
Historians have relied for too long on written sources (the letters that Pope Martin I wrote from Cherson, as well as De Administrando Imperio) to assess the economic situation in the Crimea, especially in Cherson, during the so-called Dark Ages (7th to 9th centuries). Many still believe that that city could not have survived without shipments of grain from the outside, particularly from the lands along the southern coast of the Black Sea. Seals of Byzantine officials found in Cherson tell a different story, as they indicate commercial exchanges between the Crimea and Constantinople. If the peninsula participated in trade, something must have been offered in exchange for the goods coming from the Capital. The archaeological evidence strongly suggests that during the 8th and 9th centuries, the hinterland of Cherson, as well as the Kerch Peninsula (eastern Crimea) witnessed rapid economic development, largely based on the cultivation of crops. Silos found on several settlement sites, both open and fortified, suggest a surplus, which was most likely commercialized. If so, the closest markets were across the Black Sea, to the south, primarily in Constantinople. Other commodities, such as wine transported in amphorae, traveled in the opposite direction, across the Sea of Azov and into the interior of Khazaria. In exchange, the peninsula received shipments of grain, which were then re-exported to Constantinople. Far from relying on shipments of grain from the Capital, Cherson and the rest of the Crimean Peninsula in fact supplied Constantinople with food. Numerous vats for the production of fish sauce have been found in Cherson, and many were in operation before 900. A good deal of the garum served at tables in Constantinople between the 7th and the 9th century must have come from Cherson. The archaeological evidence therefore calls for a re-assessment of the economic situation in the Crimean Peninsula during the “Dark Ages”.